Association between Internet use and adolescent behavioral development: a cross-lagged regression study - Yan, Desheng; Qi, Lei; Chen, Yao; Li, Guangming (Frontiers in Behavioral Neuroscience, 2026)
Promotive behavior refers to actions that facilitate individuals’ efforts to surmount obstacles and proactively pursue their goals, thereby fostering adaptive functioning and positive development. In contrast, prohibitive behavior refers to harmful or otherwise maladaptive actions that may hinder individuals’ personal growth and developmental outcomes. This study aims to explore the possible causal relationship between Internet use behavior and adolescent behavioral development, including promotive behavior and prohibitive behavior. There were 9,132 students’ data that were analyzed, and cross-lagged regression analysis was used to study causal relationships between two or more variables that change over time. Data were collected at two time points: T1 (2013–2014) and T2 (2014–2015), with an interval of approximately 1 year between the two waves. Results indicated a negative correlation between Internet use behavior and promotive behavior at points-in-time T1 and T2, while a positive relationship was observed between Internet use behavior and prohibitive behavior at both time points. Findings suggest that reducing problematic Internet use among adolescents contributes to the development of healthy behaviors, and active and healthy adolescent behaviors can in turn reduce their problematic Internet use.